2012
DOI: 10.4103/0019-5413.96379
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporotic profiles in elderly patients with symptomatic lumbar spinal canal stenosis

Abstract: Background:The osteoporosis and lumbar canal stenosis, in elderly patients are under diagnosed and under reported. We report a cross sectional study to demonstrate the osteoporotic profile in patients with lumbar spinal stenosis (LSS) and to determine the proportion of patients with LSS who need to be treated for osteoporosis.Materials and Methods:One hundred and six postmenopausal patients with symptomatic LSS were evaluated for osteoporotic profile, which included lumbar and hip bone mineral density (BMD), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
0
25
0
2
Order By: Relevance
“…Автори підкреслюють важливість передопераційного оцінювання МЩКТ у пацієнтів із дегенеративними захворюваннями хребта, оскільки її зниження є чинником ризику виникнення ускладнень [6]. У віковій групі понад 60 років поперековий стеноз хребтового каналу був поєднаним із показниками МЩКТ на рівні остеопорозу й остеопенії вже в 79,2 % хворих [7]. У результаті виконаних клінічних і експериментальних робіт виявлено взаємозв'язок між показниками МЩКТ тіл хребців і дегенерацією міжхребцевих дисків, проте дискусійним залишається питання, є він прямо чи обернено пропорційним [3,[8][9][10].…”
Section: в пожилом и старческом возрасте остеопороз и остеохонд роз пunclassified
See 1 more Smart Citation
“…Автори підкреслюють важливість передопераційного оцінювання МЩКТ у пацієнтів із дегенеративними захворюваннями хребта, оскільки її зниження є чинником ризику виникнення ускладнень [6]. У віковій групі понад 60 років поперековий стеноз хребтового каналу був поєднаним із показниками МЩКТ на рівні остеопорозу й остеопенії вже в 79,2 % хворих [7]. У результаті виконаних клінічних і експериментальних робіт виявлено взаємозв'язок між показниками МЩКТ тіл хребців і дегенерацією міжхребцевих дисків, проте дискусійним залишається питання, є він прямо чи обернено пропорційним [3,[8][9][10].…”
Section: в пожилом и старческом возрасте остеопороз и остеохонд роз пunclassified
“…Таким чином, результати дослідження показали зниження рівня активних метаболітів вітаміну D до «недостатності» або «дефіциту» в пацієнток постменопаузального періоду з поєднанням зниженої МЩКТ (остеопенія або остеопороз) й остеохондрозу хребта. У роботах інших авторів встановлено окремо взаємозв'язок між дегенеративними захворюваннями хребта і рівнем вітаміну D [18] або показником МЩКТ [3,6,7,14].…”
Section: матеріал і методиunclassified
“…As the population becomes older, it is common to see patients developing concurrent spinal problems such as lumbar spinal stenosis (LSS), degenerative spondylolisthesis (DSL), and osteoporotic vertebral compression fractures (VCF). These conditions often affect the same or adjacent regions of the thoracic and lumbar spine [ 1 - 3 ]. Large radiologic and anatomic studies have shown a biphasic distribution of VCF with 45% to 55% found in the mid-thoracic spine from T6 to T8, and 10% to 20% from T12 to L2 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, according to our literature search, few studies have been devoted to degenerative diseases of the spine. Yet, some recent reports in this area have indicated a high prevalence of vitamin D deficiency in these patients [78910]. …”
Section: Introductionmentioning
confidence: 99%